The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00464-021-08429-7
|View full text |Cite
|
Sign up to set email alerts
|

Remote training in laparoscopy: a randomized trial comparing home-based self-regulated training to centralized instructor-regulated training

Abstract: Background Simulation-based surgical training (SBST) is key to securing future surgical expertise. Proficiency-based training (PBT) in laparoscopy has shown promising results on skills transfer. However, time constraints and limited possibilities for distributed training constitute barriers to effective PBT. Home-based training may provide a solution to these barriers and may be a feasible alternative to centralized training in times of assembly constraints. Methods We randomly assigned first-year trainees in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
0
11
1
Order By: Relevance
“…Several additional small studies assessing remote training for surgical skills have also been reported. These generally involve the teaching of basic surgical skills using box trainers such as peg transfer, knot tying, and suturing techniques under laparoscopy (25,26). Recently a course utilizing remote guidance of actual endovascular surgery using augmented reality (AR), has also been published (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several additional small studies assessing remote training for surgical skills have also been reported. These generally involve the teaching of basic surgical skills using box trainers such as peg transfer, knot tying, and suturing techniques under laparoscopy (25,26). Recently a course utilizing remote guidance of actual endovascular surgery using augmented reality (AR), has also been published (27).…”
Section: Discussionmentioning
confidence: 99%
“…In an online interactive basic surgical skills course, medical students were able to demonstrate proficiency in knot tying and simple suturing and were satisfied with this learning method 9. Additionally, a randomized controlled trial was conducted that evaluated the difference between centralized, instructor-regulated training and “home-based, self-regulated training” in laparoscopy 19. The authors reported that surgical trainees who participated in “home-based, self-regulated training” had a 9% higher passing rate than those in the instructor-led group, suggesting that individual learning is as effective as didactic and in-person instruction in laparoscopy 19.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, a randomized controlled trial was conducted that evaluated the difference between centralized, instructor-regulated training and "home-based, self-regulated training" in laparoscopy. 19 The authors reported that surgical trainees who participated in "home-based, self-regulated training" had a 9% higher passing rate than those in the instructor-led group, suggesting that individual learning is as effective as didactic and inperson instruction in laparoscopy. 19 However, a survey of medical and dental students revealed that more students (73.5%) were satisfied with traditional anatomy education than online lectures (56%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informants were regularly invited on a voluntary basis among trainees participating in a six-week simulationbased laparoscopic skills training program. The training was situated and facilitated in two ways, i.e., by centralised or remote training, based on a previously published randomised comparative study investigating training patterns and performance outcomes between the two training modalities [24]. The training was structured as PBT, and training equipment was the same between groups.…”
Section: Context and Samplementioning
confidence: 99%